REGULATORY PROBLEMS OF DISASTER MANAGEMENT IN INDONESIA - Shanti Dwi Kartika (Jurnal Dinamika Hukum, 2017)
Indonesia is a disaster-prone country. The disaster may affect the economy, welfare, and politics of the country. By that reason, the state should protect the people and pay more attention to disaster management through legal instruments. Symptoms in the community are pushing the politics of law in this country by the issuance of legal policy in form of Law Number 24 Year 2007 on Disaster Management. Therefore, it is important to understand about regulatory aspect of disaster management, legal issue in the implementation of disaster management, and problem solving from that legal issue. This study determined that the recent law of disaster management has been well improved following the previous law. In its implementation, there are still problems such as disharmony legislation in disaster management, overlapping authority and lack of inter-institutional coordination followed by overlapping authority, disoriented working procedures of disaster management and disaster management to uncontrolled funding.